2016
DOI: 10.1117/1.jmi.3.3.035501
|View full text |Cite
|
Sign up to set email alerts
|

Numerical observer for atherosclerotic plaque classification in spectral computed tomography

Abstract: Abstract. Spectral computed tomography (SCT) generates better image quality than conventional computed tomography (CT). It has overcome several limitations for imaging atherosclerotic plaque. However, the literature evaluating the performance of SCT based on objective image assessment is very limited for the task of discriminating plaques. We developed a numerical-observer method and used it to assess performance on discrimination vulnerable-plaque features and compared the performance among multienergy CT (ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Second, the findings are relevant to the development of model observers. Many groups are currently working the development of model observers for 3D image modalities [26] including digital breast tomosynthesis [27]–[29] and computed tomography [30], [31]. Our results suggest that model observers for 3D images require taking into account visual processing in the periphery.…”
Section: Discussionmentioning
confidence: 87%
“…Second, the findings are relevant to the development of model observers. Many groups are currently working the development of model observers for 3D image modalities [26] including digital breast tomosynthesis [27]–[29] and computed tomography [30], [31]. Our results suggest that model observers for 3D images require taking into account visual processing in the periphery.…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, the present study is the first time the GSI technique has been adopted to analyze the calcium content in carotid atherosclerotic plaque. In the present study, this novel technique was selected because, inheriting the detection sensitivity of CT towards calcium, GSI uses X-rays and expresses the absorption of the energy spectrum based on tissue composition and lesions, performing quantitative analysis via the MD technique, where the calcium map displays only calcium density and enables measurement of calcium content in plaques ( 7 , 8 ). Of note, the present study also indicated that the spectral curve slope of the CT value of the plaque in patients with stable plaques was significantly lower than that of patients with unstable plaques, which is in agreement with a previous study by Karçaaltıncaba and Aktaş ( 18 ), who reported that vulnerable plaques were rich in lipid cores and their energy spectrum curve exhibited a bow-up curve with a positive slope, whereas stable plaques had a bow-down curve with a negative slope.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, GSI holds great potential to better characterize and quantify the concentration of plaque components, such as lipids, calcification and fibrous tissues ( 8 ), in order to accurately distinguish vulnerable plaques from stable plaques in carotid arteries. A recent study by Shinohara et al ( 9 ) compared the applicability of GSI to that of 3D time-of-flight magnetic resonance angiography (MRA) in patients with carotid artery stenosis, revealing that the effective Z-value of noncalcified carotid plaques was markedly lower in the group with high signal intensity than that in the group with low signal intensity on MRA.…”
Section: Introductionmentioning
confidence: 99%
“…Among these neuroimaging technologies, a novel gemstone spectral imaging (GSI) that incorporates computed tomographic angiography (CTA) with a gemstone detector, received increasing attention in recent years, as it allow for both monochromatic energy imaging and material basis decomposition. More importantly, GSI holds great potential to better characterize and quantify the concentration of the plaque components such as lipid, calci cation and brous tissue [12], so as to accurately distinguish vulnerable plaques from stable plaques in carotid arteries. However, fewer studies have been conducted to investigate the role of GSI in assessment of vulnerable carotid plaque.…”
Section: Introductionmentioning
confidence: 99%